Comparison of oxygen saturation measured by pulse oximetry and arterial blood gas analysis in neonates - Srie Yanda; Munar Lubis; Yoyoh Yusroh (Paediatrica Indonesiana, 2003)
Background Arterial blood gas is usually beneficial to discern thenature of gas exchange disturbances, the effectiveness of com-pensation, and is required for adequate management. AlthoughPaO 2 is the standard measurement of blood oxygenation, oxygensaturation measured by pulse oximetry (SapO 2 ) is now a custom-ary noninvasive assessment of blood oxygenation in newborn in-fants.Objective To compare oxygen saturation measured by pulse oxi-metry (SapO 2 ) and arterial blood gas (SaO 2 ), its correlation withother variables, and to predict arterial partial pressure of oxygen(PaO 2 ) based on SapO 2 values.Methods A cross sectional study was conducted on all neonatesadmitted to Pediatric Intensive Care Unit (PICU) during February2001 to May 2002. Neonates were excluded if they had impairedperipheral perfusion and/or congenital heart defects. Paired t-testwas used to compare SapO 2 with SaO 2 . Correlation between twoquantitative data was performed using Pearson’s correlation. Re-gression analysis was used to predict PaO 2 based on SapO 2 val-ues.Results Thirty neonates were included in this study. The differ-ence between SaO 2 and SapO 2 was significant . There were sig-nificant positive correlations between heart rate /pulse rate andTCO 2 , HCO 3 ; respiratory rate and TCO 2 , HCO 3 , base excess (BE);core temperature and HCO 3 , BE; surface temperature and pH,TCO 2, HCO 3, BE; SapO 2 and pH, PaO 2 ; and significant negativecorrelation between SapO 2 and PaCO 2 ; the correlations were weak.The linear regression equation to predict PaO 2 based on SapO 2values was PaO 2 = -79.828 + 1.912 SapO 2 .Conclusion Pulse oximetry could not be used in place of arterialblood gas analysis available for clinical purpose